Social media and expressive citizenship: Understanding the relationships between social and entertainment expression on Facebook and political participation - Yu, Rebecca Ping; Oh, Yu Won (Telematics and informatics, 2018)
•Social and entertainment expressive use positively relate to political expression.•Social expressive use positively relates to political talk.•Social and entertainment expression link to political actions via communication.•Political interest plays little role in moderating these relationships. Substantial research has explored the political significance of social media use in the context of collective actions. Yet much remains unknown about whether common, day-to-day, nonpolitically oriented activities on social media relate to political engagement. Focusing on Facebook, the primary social media platform for most Americans, this study investigates whether and how social and entertainment expression on the site are associated with political participation among a diverse online sample of American adults. Results show that social and entertainment expressive Facebook use are indirectly associated with political participation through political communication in the form of interactive political expression on the site. In addition, findings demonstrate that social expressive use is also conducive to political participation via offline political talk, but entertainment expressive use is not significantly related to political talk in offline settings. Further analysis shows that the interactions between political interest and each of the expressive uses are largely insignificantly related to political communication and participation. Overall, the study’s findings help to clarify the distinctions between the two types of nonpolitical Facebook use and the underlying process by which these uses contribute to political participation.